Gaze pursuit and arm control of adolescent males diagnosed with attention deficit hyperactivity disorder (ADHD) and normal controls: evidence of a dissociation in processing visual information of short and long duration - Vickers, J. N.; Rodrigues, Sérgio Tosi [UNESP]; Brown, L. N. (Taylor & Francis Ltd, 2002)
Three-dimensional kinematic analysis of line of gaze, arm and ball was used to describe the visual and motor behaviour of male adolescents diagnosed with attention deficit hyperactivity disorder (ADHD). The ADHD participants were tested when both on (ADHD-On) and off (ADHD-Off) their medication and compared to age-matched normal controls in a modified table tennis task that required tracking the ball and hitting to cued right and left targets. Long-duration information was provided by a pre-cue, in which the target was illuminated approximately 2 s before the serve, and short-duration information by an early-cue illuminated about 350 ms after the serve, leaving -500 ms to select the target and perform the action. The ADHD groups differed significantly from the control group in both the pre-cue and early-cue conditions in being less accurate, in having a later onset and duration of pursuit tracking, and a higher frequency of gaze on and off the ball. The use of medication significantly reduced the gaze frequency of the ADHD participants, but surprisingly this did not lead to an increase in pursuit tracking, suggesting a barrier was reached beyond which ball flight information could not be processed. The control and ADHD groups did not differ in arm movement onset, duration and velocity in the short-duration early-cue condition; in the long-duration pre-cue condition, however, the ADHD group's movement time onset and arm velocity differed significantly from controls. The results show that the ADHD groups were able to process short-duration information without experiencing adverse effects on their motor behaviour; however, long-duration information contributed to irregular movement control.
Keywords: eye movements; methylphenidate; motor coordination; pursuit tracking